(untitled) (Revista Contexto & Saúde, 2020)
Lawsuits regarding oncologic drugs are a growing reality in Brazil, causing great financial impact in the public administration. Due to the high cost associated with these drugs, in addition to the high complexity of the treatment, an insightful technical analysis is necessary to ensure the efficacy of the treatment, as well as the justifiable use of public money. The goal of this work was to analyze the profile of the lawsuit demands answered in the oncology sector of the UFPel School Hospital, along with the financial impact of these lawsuits to the public coffers. From January of 2017 to August of 2019 the oncology sector complied with 146 judicial decisions, with a total cost of nearly R 11,439,544.00 to the public coffers. In descending order, the drugs that were judicially demanded more often were: bortezomib, abiraterone, bevacizumab, trastuzumab, rituximab and pazopanib; being multiple myeloma, prostate cancer, colorectal cancer, breast cancer and kidney cancer the most prevalent malignancies. It is made evident that the effects are negative for the public administration as it generates budgetary and financial imbalances. However, this work points towards problems involved in the process, as well as strategies that can possibly be applied in short and long term by federative, judiciary and assistance entities, in order to minimize the negative consequences of the judicialization while ensuring to the citizen all their rights determined by law.